The rs2175898 Polymorphism in the ESR1 Gene has a Significant Sex-Specific Effect on Obesity - Guclu-Geyik, Filiz; Coban, Neslihan; Can, Gunay; Erginel-Unaltuna, Nihan (Biochemical genetics, 2020)
Polymorphisms in the ESR1 gene have been associated with obesity and lipid metabolism. There are also important sex-related differences in the prevalence of obesity and related phenotypes. Therefore, we aimed to interrogate the association of the ESR1 rs2175898 gene polymorphism with obesity, obesity-related variables, and lipid levels in men and women as separate groups. Two thousand twenty-two randomly selected middle-aged and elderly Turks were genotyped for ESR1 rs2175898 polymorphism using real-time polymerase chain reaction with hybridization probes. We found sex-related differences of the ESR1 rs2175898 polymorphism in obesity. Logistic regression analysis after adjustment for age, smoking status, physical activity, diabetes mellitus, and the presence of menopause status in women demonstrated significantly decreased risk for obesity in female AG genotype carriers (OR 0.69; 95% CI 0.52–0.91; p = 0.010), and in male GG genotype carriers (OR 0.49; 95% CI 0.25–0.96; p = 0.039), Furthermore, carriers of the rs2175898 G allele exhibited a lower body mass index in both sexes and decreased waist circumference in women but not in men. Our findings also showed significantly higher serum total-C levels ( p = 0.007) in the carriers of the AG+GG/AG genotype compared with the AA genotype in men. The AG genotype of the ESR1 rs2175898 polymorphism in women and GG genotype in men were found to have a decreased likelihood for obesity compared with the other rs2175898 genotypes.